Characteristics and outcomes of avoidant/restrictive food intake disorder in Japanese elementary‐school students on total parenteral nutrition - Akira Tamura; Koichi Minami; Yuko Tsuda; Hiroshi Tsujimoto; Takayuki Ichikawa; Kazuhiro Mizumoto; Hiroyuki Suzuki (Wiley, 2021)
ABSTRACT The clinical outcomes of adolescents with avoidant/restrictive food intake disorder (ARFID) remain unclear. Furthermore, no report has compared the characteristics of ARFID and restricting‐type anorexia nervosa (R‐AN) in elementary‐school students on total parenteral nutrition (TPN). This study retrospectively reviewed inpatients diagnosed with ARFID or R‐AN between 2005 and 2019. Patients with ARFID (two boys and seven girls) and R‐AN (13 girls) were hospitalized because of rapid physical deterioration, and nutrition therapy was continued without withdrawal. The ARFID group exhibited significantly lower body weights at admission than the R‐AN group and gained an average of 6.5 kg during hospitalization; furthermore, the monthly weight gain during hospitalization was significantly higher, and no relapse was observed. Early physical improvement in ARFID resulted in good recovery. In conclusion, TPN can be easily introduced to patients with ARFID, in whom aversive eating is a concern, and is a suitable treatment for ARFID.